Oxidative stress in entomopathogenic fungi grown on insect-like hydrocarbons - Huarte Bonnet, Carla (2014)
Entomopathogenic fungi mostly attack their insect hosts by penetration through the cuticle. The outermost insect surface is covered by a lipid-rich layer, usually composed of very long chain hydrocarbons. These fungi are apt to grow on straight chain hydrocarbons (alkanes) as the sole carbon source. Insect-like hydrocarbons are first hydroxylated by a microsomal P450 monooxygenase system, and then fully catabolized by peroxisomal β-oxidation reactions in Beauveria bassiana. In this review, we will discuss lipid metabolism adaptations in alkane-grown fungi, and how an oxidative stress scenario is established under these conditions. Fungi have to pay a high cost for hydrocarbon utilization; high levels of reactive oxygen species are produced and a concomitant antioxidant response is triggered in fungal cells to cope with this drawback.